К истории концепта “Общество как государственное установление”: Памяти Дитриха Гайера (1928-2023) - Майя Лавринович; Ингрид Ширле (Вивліоѳика)
Dietrich Geyer’s article “‘Gesellschaft’ als staatliche Veranstaltung. Sozialgeschichtliche Aspekte des russischen Behördenstaats im 18. Jahrhundert,” had a significant impact on both German and American historiography, which is not the case with the Soviet historiography of the 1960-1980s. Nevertheless, late Soviet and early post-Soviet historiography was preoccupied with the same problems of the relationship between “state” and “society” in Imperial Russia and sometimes followed the line of D. Geyer’s thinking. In the 1990s, when the “grand narrative” of modernization was called into question, historians engaged in a polemic about the very productiveness of the opposition of “state” and “society” as categories of historical knowledge. They turned to the local level of late imperial Russian society, or adopted new methods of examining legislative sources, avoiding access to “backwardness” or “underdevelopment,” preferring to examine the language and rhetoric of eighteenth-century documents.